2002
DOI: 10.1046/j.1464-5491.2002.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum fructosamine as a marker of 5‐year risk of developing diabetes mellitus in patients exhibiting stress hyperglycaemia

Abstract: The level of RSG in stress hyperglycaemia does not predict the future development of DM. Raised serum fructosamine is a more useful marker of future DM risk than RSG alone. Further prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Both antibodies were purified from cell lines provided by Dr. O'Connor (Columbia University, New York, NY). B152 was biotinylated with long-chain NHS-biotin (13 ), and B207 was conjugated with acridinium ester (14 ).…”
mentioning
confidence: 99%
“…Both antibodies were purified from cell lines provided by Dr. O'Connor (Columbia University, New York, NY). B152 was biotinylated with long-chain NHS-biotin (13 ), and B207 was conjugated with acridinium ester (14 ).…”
mentioning
confidence: 99%
“…With regards to blood glucose levels, studies in humans have shown that stress-induced hyperglycemia correlates with subsequent development of diabetes and that the subjects who were predisposed to develop glucose intolerance during the FSIVGTT had higher fructosamine levels at baseline. [ 70 ] As mentioned above, the IR pigs appeared to exhibit stress-associated hyperglycemia during the Bergman FSIVGTT that may have accounted for some portion of the higher fructosamine levels. Fructosamine has also been shown to correlate with 2 hr postprandial glucose[ 71 ] and relatively short periods of hyperglycemia have been shown to increase protein glycation even if fasting glucose is not increased.…”
Section: Discussionmentioning
confidence: 98%
“…It is also important to note that a conclusion regarding the unsuitability of these markers for assessing variation in glycemic exposures in individuals without diabetes is not an assessment of their potential value as markers of disease risk in this population. Variation in each of these markers has been reported to be significantly associated with future risk of diabetes or cardiovascular disease in populations without diabetes ( 68 , 113 , 114 ).…”
Section: Discussionmentioning
confidence: 99%